Effects of variability in structural and seismic factors on the seismic fragility of reinforced concrete poles in Peruvian electrical substations - Ruiz Esquivel, Jose Oscar (2025)
This study analyzes the seismic fragility of Peruvian electrical substations by applying fragility functions generated with multiple nonlinear dynamic time-history analyses, with respect to the structural variability of concrete compressive strength (f'c) and yield strength of the reinforcing steel (fy), and the uncertainty in a seismic factor of peak ground acceleration (PGA). The study, with a quantitative approach and experimental design, was applied and explanatory in scope. The random method was considered for the generation of 2000 samples of structural factors and 2000 artificial accelerograms of spectro-compatible earthquakes compatible with real Peruvian signals. The calculations reveal that maximum displacements (Dmax), maximum drifts (Δmax) and shear forces at the base (Vb) are more conservative than in previous studies, attributable to nonlinear modeling with plastic hinges of different typologies and the cyclic effect of the earthquake. To define fragility, four damage states (ED) were proposed, with ED1 and ED2 presenting damage probabilities (PD) like those in previous studies. Upon inspection, ED3 and ED4 represent yielding and collapse, and it was observed that 50% of their PD are exceeded for PGA values greater than 0.24g and 0.53g, respectively. The proposed methodology demonstrated the influence of concrete and reinforcing steel on the structural response, generating coherent fragility curves that strengthen seismic assessment and earthquake risk management.